PEMANFAATAN LIMBAH PADI (Oryza Sativa L) UNTUK PEMBUATAN SILIKA GEL DENGAN VARIASI RASIO MASSA BAHAN BAKU DAN LARUTAN PEREAKSI: PEMANFAATAN LIMBAH PADI (Oryza Sativa L) UNTUK PEMBUATAN SILIKA GEL DENGAN VARIASI RASIO MASSA BAHAN BAKU DAN LARUTAN PEREAKSI (Chempublish Journal, 2026)
Rice is one of the major agricultural commodities that generates large amounts of biomass waste, particularly rice husks and rice straw. These by-products contain high silica content and have potential as raw materials for silica gel production. This study aimed to synthesize silica gel from rice husks and rice straw using the sol–gel method with different biomass ratios and acid activators. The ratios of rice husk to rice straw used were 100:0, 75:25, 50:50, 25:75, and 0:100 (w/w). The synthesis process was carried out using 3 M HCl and 3 M H₂SO₄ solutions as reactants. The obtained silica gel products were evaluated based on yield, moisture content, water adsorption capacity, and functional group characteristics using Fourier Transform Infrared (FTIR) spectroscopy. The results showed that the optimum silica gel was produced from a biomass ratio of 75 % rice husk and 25 % rice straw using H₂SO₄ as the reactant. The resulting silica gel exhibited a yield of 82.5 %, moisture content of 14.7 %, and water adsorption capacity of 0.0092 g/g. FTIR analysis confirmed the presence of silanol (Si–OH), siloxane (Si–O–Si), and siloxy functional groups, indicating successful silica gel formation. Overall, the synthesized silica gel demonstrated physicochemical properties consistent with standard silica gel characteristics and showed potential for application as an adsorbent material.